2008
DOI: 10.1128/jvi.01212-08
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-Independent Expression of Immediate-Early Gene 3 Results in G 1 and G 2 Arrest in Murine Cytomegalovirus-Infected Cells

Abstract: The infectious cycle of human cytomegalovirus (HCMV) is intricately linked to the host's cell cycle. Viral gene expression can be initiated only in G 0 /G 1 phase. Once expressed, the immediate-early gene product IE2 prevents cellular DNA synthesis, arresting infected cells with a G 1 DNA content. This function is required for efficient viral replication in vitro. A prerequisite for addressing its in vivo relevance is the characterization of cell cycle-regulatory activities of CMV species for which animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 71 publications
2
37
0
Order By: Relevance
“…Despite the presence of a pp150 homolog (M32), gene expression of murine CMV (MCMV) occurs both in a cell cycle and cyclin A2-independent manner (10,15). Aiming for evolutionary insight into HCMV's cell cycle dependency, we compared known pp150 homologs of mammalian CMVs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the presence of a pp150 homolog (M32), gene expression of murine CMV (MCMV) occurs both in a cell cycle and cyclin A2-independent manner (10,15). Aiming for evolutionary insight into HCMV's cell cycle dependency, we compared known pp150 homologs of mammalian CMVs.…”
Section: Resultsmentioning
confidence: 99%
“…It complements previous studies on the role of p53-p21-CDK signaling (9, 10) by adding a viral sensor molecule to this pathway. It explains why MCMV, used in the most common animal models of HCMV infection, was found to be less sensitive to varying cell cycle conditions and differentiation states (10,15,21) and it helps to understand the limited efficacy of HDAC inhibition or Daxx knockdown in desilencing IE gene expression in pluripotent cells (6).…”
Section: Discussionmentioning
confidence: 99%
“…Although wt MCMV infection results in G 1 and G 2 arrest and the ⌬ie3 virus has lost this ability, ectopically expressed pIE611 exhibits cell cycle arrest activity only in G 1 and not G 2 (29), exemplifying the occasion for reevaluation. Our findings open up the possibility to dissect the individual impact of each IE3 isoform for CMV pathogenesis and host cell interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Due to IE2-responsive promoter elements within the viral origin of replication (oriLyt), IE2 is also directly involved in the initiation of viral DNA synthesis (77). Therefore, IE2 has attracted considerable interest as an antiviral target (66, 74), and an IE2-specific antisense RNA is already in clinical use for the treatment of HCMV retinitis (26).Recently, we and others have shown that cells in the S/G 2 phase of the cell division cycle exhibit a broad block to HCMV IE gene expression (14,55,73). This block acts at the mRNA expression level and affects not only IE1 and IE2, but also other IE gene loci, like .…”
mentioning
confidence: 99%